Law, state and religion in the new Europe : debates and dilemmas - Zucca, Lorenzo; Ungureanu, Camil (Cambridge : Cambridge University Press, 2012)
'The return of religion to the public sphere raises various dilemmas. Rights and values, pluralism and identity, justice and efficacy, autonomy and tradition, and integration and toleration cannot always be balanced without the loss of something valuable. This volume of essays tackles such dilemmas from two perspectives. To begin, major contemporary theorists rethink the place of religion in the public sphere from republican, liberal and critical-theoretical viewpoints. Contributors then bring together theory and practice to better conceptualize and assess the latest developments in European jurisprudence with respect to religion'--
Includes bibliographical references and index.
Keywords: Freedom of religion -- Europe; Religion and law -- Europe; Church and state -- Europe